AutonomROS: A ReconROS-based Autonomous Driving Unit - Lienen, Christian; Brede, Mathis; Karger, Daniel; Koch, Kevin; Logan, Dalisha; Mazur, Janet; Nowosad, Alexander Philipp; Schnelle, Alexander; Waizy, Mohness; Platzner, Marco (2023 Seventh IEEE International Conference on Robotic Computing (IRC))

On Guaranteeing Schedulability of Periodic Real-time Hardware Tasks under ReconOS64 - Clausing, Lennart; Guetattfi, Zakarya; Kaufmann, Paul; Lienen, Christian; Platzner, Marco (Proceedings of the 19th International Symposium on Applied Reconfigurable Computing (ARC))

Mapping and Optimizing Communication in ROS 2-based Applications on Configurable System-on-Chip Platforms - Lienen, Christian; Nowosad, Alexander Philipp; Platzner, Marco (Proceedings of the 2023 9th International Conference on Robotics and Artificial Intelligence (ICRAI))

fpgaDDS: An Intra-FPGA Data Distribution Service for ROS 2 Robotics Applications - Lienen, Christian; Middeke, Sorel Horst; Platzner, Marco (Proceedings of the 2023 IEEE/RSJ International Conference on Intelligent Robots and Systems (IROS))

Towards comparable ratings: Exploring bias in German physician reviews - Kersting, Joschka; Maoro, Falk; Geierhos, Michaela (Data & Knowledge Engineering)
In this study, we evaluate the impact of gender-biased data from German-language physician reviews on the fairness of fine-tuned language models. For two different downstream tasks, we use data reported to be gender biased and aggregate it with annotations. First, we propose a new approach to aspect-based sentiment analysis that allows identifying, extracting, and classifying implicit and explicit aspect phrases and their polarity within a single model. The second task we present is grade prediction, where we predict the overall grade of a review on the basis of the review text. For both tasks, we train numerous transformer models and evaluate their performance. The aggregation of sensitive attributes, such as a physician’s gender and migration background, with individual text reviews allows us to measure the performance of the models with respect to these sensitive groups. These group-wise performance measures act as extrinsic bias measures for our downstream tasks. In addition, we translate several gender-specific templates of the intrinsic bias metrics into the German language and evaluate our fine-tuned models. Based on this set of tasks, fine-tuned models, and intrinsic and extrinsic bias measures, we perform correlation analyses between intrinsic and extrinsic bias measures. In terms of sensitive groups and effect sizes, our bias measure results show different directions. Furthermore, correlations between measures of intrinsic and extrinsic bias can be observed in different directions. This leads us to conclude that gender-biased data does not inherently lead to biased models. Other variables, such as template dependency for intrinsic measures and label distribution in the data, must be taken into account as they strongly influence the metric results. Therefore, we suggest that metrics and templates should be chosen according to the given task and the biases to be assessed.
Keywords: Language model fairness; Aspect phrase classification; Grade prediction; Physician reviews

Characterizing external visualization in mathematics education research: a scoping review - Schoenherr, Johanna; Schukajlow, Stanislaw (ZDM – Mathematics Education)
Abstract External visualization (i.e., physically embodied visualization) is central to the teaching and learning of mathematics. As external visualization is an important part of mathematics at all levels of education, it is diverse, and research on external visualization has become a wide and complex field. The aim of this scoping review is to characterize external visualizations in recent mathematics education research in order to develop a common ground and guide future research. A qualitative content analysis of the full texts of 130 studies published between 2018 and 2022 applied a deductive-inductive coding procedure to assess four dimensions: visualization product or process, type of visualization, media, and purpose. The analysis revealed different types of external visualizations including visualizations with physical resemblance ranging from pictorial to abstract visualizations as well as three types of visualizations with structural resemblance: length, area, and relational visualizations. Future research should include measures of visualization products or processes to help explain the demands and affordances that different types of visualizations present to learners and teachers.
Keywords: General Mathematics; Education

Verifying Software and Reconfigurable Hardware Services - Wehrheim, Heike; Platzner, Marco; Bodden, Eric; Schubert, Philipp; Pauck, Felix; Jakobs, Marie-Christine (On-The-Fly Computing -- Individualized IT-services in dynamic markets)

Compute Centers I: Heterogeneous Execution Environments - Hansmeier, Tim; Kenter, Tobias; Meyer, Marius; Riebler, Heinrich; Platzner, Marco; Plessl, Christian (On-The-Fly Computing -- Individualized IT-services in dynamic markets)

Flexible Industrial Analytics on Reconfigurable Systems-On-Chip - Boschmann, Alexander; Clausing, Lennart; Jentzsch, Felix; Ghasemzadeh Mohammadi, Hassan; Platzner, Marco (On-The-Fly Computing -- Individualized IT-services in dynamic markets)

Die Rechtsnatur elektronischer Wertpapiere - Bartlitz, David (Zeitschrift für Unternehmens- und Gesellschaftsrecht (ZGR))

ABHÄNGEN - Ein- und Ausgrenzen, Kanonisieren, Kollaborieren in Pop, Kunst und Medien - Jacke, Christoph (Impulse. Texte und Bilder zur Kunstvermittlung)

Abhängenwerden. Fühlen und Denken - Jacke, Christoph (Impulse. Texte und Bilder zur Kunstvermittlung)

Editorial - Jacke, Christoph; Pickartz, Tim; Autsch, Sabiene (Impulse. Texte und Bilder zur Kunstvermittlung)

Abhängenwerden. Fühlen und Denken. - Jacke, Christoph (Impulse. Texte und Bilder zur Kunstvermittlung.)

Tiere in der Theologie? Zur Überwindung der Tiervergessenheit. Der Blog des Zentrums für Komparative Theologie und Kulturwissenschaften - Herdramm, Henrike (BloKK. Der Blog des Zentrums für Komparative Theologie und Kulturwissenschaften)

Monocular visual simultaneous localization and mapping: (r)evolution from geometry to deep learning-based pipelines - Álvarez-Tuñón, Olaya; Brodskiy, Yury; Kayacan, Erdal (IEEE Transactions on Artificial Intelligence)

MIMIR-UW: A Multipurpose Synthetic Dataset for Underwater Navigation and Inspection - Álvarez-Tuñón, Olaya; Kanner, Hemanth; Marnet, Luiza Ribeiro; Pham, Huy Xuan; le Fevre Sejersen, Jonas; Brodskiy, Yury; Kayacan, Erdal (2023 IEEE/RSJ International Conference on Intelligent Robots and Systems (IROS))

PredictiveSLAM - Robust Visual SLAM Through Trajectory-Aware Object Masking - Heiß, Micha; Hansen, Jakob Grimm; Li, Dengyun; Kozłowski, Michał; Kayacan, Erdal (2023 International Conference on Unmanned Aircraft Systems (ICUAS))

CAMETA: Conflict-Aware Multi-Agent Estimated Time of Arrival Prediction for Mobile Robots - le Fevre Sejersen, Jonas; Kayacan, Erdal (2023 IEEE/RSJ International Conference on Intelligent Robots and Systems (IROS))

„Dass so was halt nie, nie wieder passiert…“ – Zum didaktisch perspektivierten rassismuskritischen Potenzial von Holocaust-Bilderbüchern zur Erinnerungsfigur Anne Frank. - Kruse, Iris; Kanning, Julian (Rassismussensibler Literaturunterricht. Grundlagen, Dimensionen, Herausforderungen, Möglichkeiten.)